Ternary positive electrode material, preparation method thereof and lithium ion battery

CN122950464APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510885661.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]目前的三元锂电池正极材料在高压下表面结构不稳定,导致材料循环变差,过渡金属容易溶出,如何改善上述问题提高三元锂电池正极材料的充电电压上限,进而有效提高三元锂电池的能量密度是本领域目前亟需解决的问题

Benefits of technology

[0042]与现有技术相比,本发明提供了一种三元正极材料,本发明通过在三元正极材料中引入F掺杂,F的高电负性可以形成比TM-O更强的TM-F过渡金属键(TM指过渡金属),提升材料表面结构稳定性,抑制过渡金属溶出,改善材料在高压下结构衰减和产气。另一方面,磷酸盐的包覆可获得具有高稳定性核壳结构的正极材料。具有三维开放框架的金属磷酸盐作为表面包覆层,在正极材料表面构建了较稳定的界面层,可以防止电极材料和电解液的直接接触,抑制高压下界面副反应,改善材料循环性能。试验结果表明,电压范围为2.8~4.45V时,采用本发明提供的三元正极材料制备的锂离子电池,在相同循环测试条件下过渡金属溶出大幅减少,容量保持率得到有效提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of lithium battery technology, and more particularly to a ternary cathode material, its preparation method, and a lithium-ion battery. The ternary cathode material has the molecular formula shown in Formula I: LiNi a Co b Mn c O 2‑0.5d F d @M x (PO4) y Formula I. This invention introduces F doping into the ternary cathode material. The high electronegativity of F allows for the formation of stronger TM-F transition metal bonds than TM-O, improving the surface structural stability of the material, suppressing transition metal dissolution, and mitigating structural degradation and gas generation under high voltage. Furthermore, phosphate coating yields a cathode material with a highly stable core-shell structure. The metal phosphate with its three-dimensional open framework serves as a surface coating layer, constructing a relatively stable interface layer on the cathode material surface. This prevents direct contact between the electrode material and the electrolyte, suppresses interfacial side reactions under high voltage, and improves the material's cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and in particular to a ternary cathode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries possess advantages such as high energy density, long cycle life, and no memory effect, making them widely used in various portable electronic devices and vehicles. Among them, ternary lithium batteries are a type of lithium-ion battery whose positive electrode material is composed of nickel (Ni), cobalt (Co), and manganese (Mn) or nickel (Ni), cobalt (Co), and aluminum (Al), hence the name ternary lithium battery. Ternary high-nickel lithium-ion batteries are attracting increasing attention due to their high energy density, high operating voltage, and good kinetic performance, and represent the future development trend of lithium-ion batteries.

[0003] Cathode materials are an integral part of lithium-ion battery components and directly affect the performance of lithium-ion batteries. Therefore, the development of cathode materials with high structural stability, high specific capacity, and good kinetics is of great significance to the development of lithium-ion batteries.

[0004] The surface structure of current ternary lithium battery cathode materials is unstable under high voltage, resulting in poor material cycling and easy dissolution of transition metals. How to improve the above problems, increase the upper limit of the charging voltage of ternary lithium battery cathode materials, and thus effectively improve the energy density of ternary lithium batteries is an urgent problem to be solved in this field. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a ternary cathode material, a method for preparing the same, and a lithium-ion battery. The prepared lithium-ion battery has high cycle stability and low transition metal dissolution.

[0006] To achieve the above objectives, the present invention provides a ternary cathode material having the molecular formula shown in Formula I:

[0007] LiNi a Co b Mn c O 2-0.5d F d @M x (PO4) y Formula I;

[0008] In Equation I, 0 < d ≤ 0.02, a + b + c = 1;

[0009] M is a metal ion;

[0010] The valence state of M is z+, and x and y satisfy: x = 3y / z.

[0011] In some embodiments, 0.01 ≤ d ≤ 0.02.

[0012] In some embodiments, M is one or more of Al ions, Mg ions, Zr ions, and Ca ions.

[0013] In some embodiments, the ternary cathode material has any of the following molecular formulas:

[0014] LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @AlPO4、LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @Mg3(PO4)2、LiNi 0.6 Co 0.1 Mn 0.3 O 1.9925 F 0.015 @AlPO4.

[0015] Another aspect of the present invention provides a method for preparing the above-mentioned ternary cathode material, comprising the following steps:

[0016] S1) In the presence of a precipitant and a complexing agent, Ni source, Co source, Mn source and F source are mixed and subjected to a co-precipitation reaction, and after aging, a fluorine-doped ternary precursor is obtained.

[0017] S2) The above-mentioned fluorine-doped ternary precursor and Li source are mixed and sintered for the first time to obtain fluorine-doped ternary cathode material.

[0018] S3) The above-mentioned fluorine-doped ternary cathode material is mixed with a phosphorus source and a metal source, and then sintered for a second time to obtain a ternary cathode material with a phosphate coating layer.

[0019] In some embodiments, the precipitant is selected from one or more of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide;

[0020] The complexing agent is selected from one or more of ammonia, ammonium bicarbonate, and citric acid;

[0021] The Ni source is selected from one or more of nickel nitrate, nickel sulfate, and nickel chloride;

[0022] The Co source is selected from one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride;

[0023] The Mn source is selected from one or more of manganese nitrate, manganese sulfate, and manganese chloride;

[0024] The F source is selected from one or more of ammonium fluoride, potassium fluoride, sodium fluoride, and magnesium fluoride.

[0025] In some embodiments, the temperature of the coprecipitation reaction is 50–80°C; the time of the coprecipitation reaction is 1–2 hours.

[0026] In the coprecipitation reaction, the pH value of the system is 10-13;

[0027] The coprecipitation reaction was carried out under stirring conditions;

[0028] The stirring speed is 100-400 rpm;

[0029] The aging time is 10 to 24 hours.

[0030] In some embodiments, the Li source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium acetate;

[0031] The molar ratio of the fluorine-doped ternary precursor to the molar ratio of Li in the Li source is 1:(1~1.02).

[0032] In some embodiments, the phosphorus source is selected from one or more of diammonium hydrogen phosphate and diammonium dihydrogen phosphate;

[0033] The metal source is selected from one or more of aluminum, zirconium, magnesium, and calcium sources;

[0034] The aluminum source is selected from one or more of aluminum nitrate and aluminum sulfate;

[0035] The zirconium source is selected from one or more of zirconium oxynitrate and zirconium oxide;

[0036] The magnesium source is selected from one or more of magnesium nitrate and magnesium acetate;

[0037] The calcium source is selected from one or more of calcium chloride, calcium hydroxide, and calcium oxide;

[0038] The mass of the phosphate coating layer is 0 to 6% of the mass of the fluorine-doped ternary cathode material, and is not 0.

[0039] In some embodiments, the temperature of the first sintering is 600–800°C; the heating rate of the first sintering is 2–10°C / min; the time of the first sintering is 5–20 h; and the atmosphere of the first sintering is pure oxygen.

[0040] The temperature of the second sintering is 500-800℃; the heating rate of the second sintering is 2-10℃ / min; the time of the second sintering is 2-10h; and the atmosphere of the second sintering is pure oxygen.

[0041] Another aspect of the present invention provides a lithium-ion battery, comprising the above-described ternary cathode material or the ternary cathode material prepared by the above-described preparation method.

[0042] Compared with existing technologies, this invention provides a ternary cathode material. By introducing fluorine (F) doping into the ternary cathode material, the high electronegativity of F allows for the formation of stronger TM-F transition metal bonds (TM stands for transition metal) than TM-O, improving the surface structural stability of the material, suppressing transition metal dissolution, and mitigating structural degradation and gas generation under high voltage. Furthermore, phosphate coating yields a cathode material with a highly stable core-shell structure. The metal phosphate with its three-dimensional open framework serves as a surface coating layer, constructing a relatively stable interface layer on the cathode material surface. This prevents direct contact between the electrode material and the electrolyte, suppresses interfacial side reactions under high voltage, and improves the material's cycle performance. Experimental results show that, within a voltage range of 2.8–4.45V, lithium-ion batteries prepared using the ternary cathode material provided by this invention exhibit significantly reduced transition metal dissolution and effectively improved capacity retention under the same cycle test conditions. Detailed Implementation

[0043] This invention provides a ternary cathode material having the molecular formula shown in Formula I:

[0044] LiNi a Co b Mn c O 2-0.5d F d @M x (PO4) y Formula I;

[0045] In Equation I, 0 < d ≤ 0.02, a + b + c = 1;

[0046] M is a metal ion;

[0047] The valence state of M is z+, and x and y satisfy: x = 3y / z.

[0048] Where a, b, and c represent the proportions or contents of Ni, Co, and Mn, respectively. The proportions or contents refer to molar ratios or molar contents.

[0049] In some embodiments, the ratio of a, b, and c is (4-7):1:(2-5).

[0050] In some embodiments, the ratio of a, b, and c is 4:1:5, 5:1:4, 6:1:3, or 7:1:2. Furthermore, a, b, and c satisfy a + b + c = 1.

[0051] In some embodiments, a, b, and c are 0.6, 0.1, and 0.3, respectively.

[0052] The d represents the proportion or content of element F. Both the proportion and content refer to molar ratio or molar content.

[0053] In some embodiments, 0 < d ≤ 0.02.

[0054] In some embodiments, 0.01 ≤ d ≤ 0.02.

[0055] In some embodiments, d is 0.01, 0.015, or 0.02.

[0056] F ion doping can form TM-F transition metal bonds with transition metal elements in the material, effectively suppressing transition metal dissolution. Experimental results show that F ion doping can reduce the amount of transition metal dissolution by about 50%, while effectively improving the battery capacity retention rate.

[0057] Among them, the doping amount of F ions is crucial to the material properties. Excessive F ion doping will lead to too many fluoride impurity phases and will destroy the structural stability and hinder ion / electron transport. Insufficient doping amount will not effectively reduce the dissolution of transition metals.

[0058] When the doping amount of F ions is 0.01≤d≤0.02, the material achieves the best performance, including the lowest transition metal dissolution and the highest capacity retention.

[0059] In formula I, M x (PO4) y Phosphate is used to coat the fluorine-doped ternary cathode material LiNi. a Co b Mn c O 2-0.5d F d On the outside, a core-shell structure is formed.

[0060] M is a metal ion.

[0061] In some embodiments, M is one or more of Al ions, Mg ions, Zr ions, and Ca ions. These metal ions have high ionic conductivity, which is beneficial to Li + Rapid ion transport.

[0062] The valence state of M is z+. In some embodiments, the valence state of M is 1+, 2+, 3+ or 4+, that is, z is any integer from 1 to 4.

[0063] x and y represent the ratio or content of M cations and PO4 anions, respectively. The ratio or content refers to a molar ratio or molar content. x and y satisfy: x = 3y / z, so that the M... x (PO4) yThe valence equilibrium is satisfied.

[0064] In some embodiments, x and y are 1 and 1, respectively.

[0065] In some embodiments, x and y are 3 and 2, respectively.

[0066] In some embodiments, x and y are 1 and 2, respectively.

[0067] In some embodiments, x and y are 3 and 1, respectively.

[0068] The phosphate, as a coating layer, forms a relatively stable interface layer on the surface of the cathode material, improving the stability of the cathode material and further reducing the amount of transition metal dissolution, thereby improving the battery's capacity retention rate.

[0069] In some embodiments, the fluorine-doped ternary cathode material LiNi a Co b Mn c O 2-0.5d F d It has any of the following molecular formulas:

[0070] LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 LiNi 0.6 Co 0.1 Mn 0.3 O 1.9925 F 0.015 .

[0071] The fluorine-doped ternary cathode material LiNi a Co b Mn c O 2-0.5d F d The outside can be coated with the above-mentioned phosphate M x (PO4) y .

[0072] In some embodiments, the M x (PO4) y It can be AlPO4, Mg3(PO4)2, Ca3(PO4)2 or Zr3(PO4)2.

[0073] In some embodiments, the ternary cathode material has any of the following molecular formulas:

[0074] LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @AlPO4、LiNi 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @Mg3(PO4)2、LiNi 0.6 Co 0.1 Mn 0.3 O 1.9925 F 0.015 @AlPO4.

[0075] In some embodiments, the particle size of the ternary cathode material is 1–2 μm. The phosphate M... x (PO4) y The thickness of the coating layer is 10–100 nm.

[0076] The experimental results show that the ternary cathode material provided by the present invention has high cycle stability and low metal dissolution after cycling.

[0077] This invention also provides a method for preparing the above-mentioned ternary cathode material, comprising the following steps:

[0078] S1) In the presence of a precipitant and a complexing agent, Ni source, Co source, Mn source and F source are mixed and subjected to a co-precipitation reaction, and after aging, a fluorine-doped ternary precursor is obtained.

[0079] S2) The above-mentioned fluorine-doped ternary precursor and Li source are mixed and sintered for the first time to obtain fluorine-doped ternary cathode material.

[0080] S3) The above-mentioned fluorine-doped ternary cathode material is mixed with a phosphorus source and a metal source, and then sintered for a second time to obtain a ternary cathode material with a phosphate coating layer.

[0081] In some embodiments, the precipitant is selected from one or more of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide.

[0082] In some embodiments, the complexing agent is selected from one or more of ammonia, ammonium bicarbonate, and citric acid.

[0083] In some embodiments, the Ni source is selected from one or more of nickel nitrate, nickel sulfate, and nickel chloride.

[0084] In some embodiments, the Co source is selected from one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride.

[0085] In some embodiments, the Mn source is selected from one or more of manganese nitrate, manganese sulfate, and manganese chloride.

[0086] In some embodiments, the F source is selected from one or more of ammonium fluoride, potassium fluoride, sodium fluoride, and magnesium fluoride.

[0087] In some embodiments, the temperature of the coprecipitation reaction is 50–80°C, which can be 50, 60, 70 or 80°C, or any of the above values ​​as the upper or lower limit.

[0088] In some embodiments, the coprecipitation reaction takes 1 to 2 hours, which can be 1 or 2 hours.

[0089] In some embodiments, the pH value of the system in the coprecipitation reaction is 10 to 13, which can be 10, 11, 12 or 13, or any of the above values ​​as the upper or lower limit.

[0090] In some embodiments, the coprecipitation reaction is carried out in a water bath.

[0091] In some embodiments, the coprecipitation reaction is carried out under stirring conditions.

[0092] In some embodiments, the stirring speed is 100 to 400 rpm, which can be 100, 200, 300 or 400 rpm, or any of the above values ​​as the upper or lower limit.

[0093] In some embodiments, the aging time is 10 to 24 hours, which can be 10, 12, 20 or 24 hours, or any of the above values ​​as the upper or lower limit.

[0094] The above-mentioned parameter constraints during the coprecipitation reaction process help to better form the precursor.

[0095] In some embodiments, after aging, the system is filtered, and the resulting precipitate is washed and dried to obtain a fluorine-doped ternary precursor.

[0096] In some embodiments, the filtration is vacuum filtration.

[0097] In some embodiments, the drying temperature is 80–110°C, which can be 80, 90, 100, or 110°C, or any of the above values ​​as the upper or lower limit.

[0098] In some embodiments, the drying time is 10 to 24 hours, which can be 10, 12, 15 or 24 hours, or any of the above values ​​can be the upper or lower limit of the range.

[0099] The aforementioned fluorine-doped ternary precursor is nickel-cobalt-manganese hydroxide Ni aCo b Mn c (OH) 2-d F d .

[0100] The fluorine-doped ternary precursor was then mixed with a Li source and subjected to a first sintering.

[0101] In some embodiments, the Li source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium acetate.

[0102] In some embodiments, the ratio of the molar amount of the fluorine-doped ternary precursor to the molar amount of Li in the Li source is 1:(1 to 1.02), which can be 1:1, 1:1.01, or 1:1.02, or any of the above values ​​as the upper or lower limit.

[0103] In some embodiments, the fluorine-doped ternary precursor and the Li source are mixed by ball milling.

[0104] In some embodiments, the rotational speed of the ball mill is 1000 to 5000 rpm, which can be 1000, 2000, 3000, 4000 or 5000 rpm, or any of the above values ​​as the upper or lower limit.

[0105] In some embodiments, the mixing time is 5 to 20 minutes, which can be 5, 10, 15 or 20 minutes, or any of the above values ​​as the upper or lower limit.

[0106] In some embodiments, the temperature of the first sintering is 600 to 800°C, which can be 600, 700 or 800°C, or any of the above values ​​as the upper or lower limit.

[0107] In some embodiments, the heating rate for the first sintering is 2–10 °C / min, which can be 2, 3, 4, 5, 6, 7, 8, 9, or 10 °C / min, or any of the above values ​​as the upper or lower limit. Excessive heating can easily lead to particle cracking, while excessively slow heating results in high energy consumption.

[0108] In some embodiments, the first sintering time is 5 to 20 hours, which can be 5, 10, 15 or 20 hours, or any of the above values ​​as the upper or lower limit.

[0109] In some embodiments, the atmosphere for the first sintering is pure oxygen.

[0110] By limiting parameters such as the temperature, time, and heating rate of the first sintering, this invention helps to minimize impurities in the precursor, resulting in a ternary cathode material with suitable particle size, specific surface area, and morphology, thus exhibiting optimal performance.

[0111] Then, the fluorine-doped ternary cathode material is mixed with a phosphorus source and a metal source, and then subjected to a second sintering.

[0112] In some embodiments, the phosphorus source is selected from one or more of diammonium hydrogen phosphate and diammonium dihydrogen phosphate.

[0113] In some embodiments, the metal source is selected from one or more of aluminum, zirconium, magnesium, and calcium sources.

[0114] In some embodiments, the aluminum source is selected from one or more of aluminum nitrate and aluminum sulfate.

[0115] In some embodiments, the zirconium source is selected from one or more of zirconium oxynitrate and zirconium oxide.

[0116] In some embodiments, the magnesium source is selected from one or more of magnesium nitrate and magnesium acetate.

[0117] In some embodiments, the calcium source is selected from one or more of calcium chloride, calcium hydroxide, and calcium oxide.

[0118] In some embodiments, the mass of the phosphate coating layer is 0 to 6% of the mass of the fluorine-doped ternary cathode material, and is not 0, and can be 1%, 2%, 3%, 4% or 5%, or any of the above values ​​as the upper or lower limit.

[0119] In some embodiments, the mixing of the fluorine-doped ternary cathode material with the phosphorus source and the metal source is a wet mixing process.

[0120] In some embodiments, the above-mentioned fluorine-doped ternary cathode material, phosphorus source, and metal source are mixed in a solvent, the material ratio is adjusted so that the amount of phosphorus source and metal source meets the phosphate content in the product, and then dried.

[0121] In some embodiments, the solvent is water.

[0122] In some embodiments, the drying process involves heating to remove the solvent.

[0123] In some embodiments, the temperature for removing the solvent by heating is 80 to 100°C, which can be 80, 90 or 100°C, or any of the above values ​​can be the upper or lower limit of the range.

[0124] In some embodiments, the time for heating to remove the solvent is 12 to 24 hours, which can be 12, 18 or 24 hours, or any of the above values ​​can be the upper or lower limit of the range.

[0125] Once the above solution has completely evaporated, a second sintering process can be carried out.

[0126] In some embodiments, the temperature of the second sintering is 500 to 800°C, which can be 500, 600, 700 or 800°C, or any of the above values ​​as the upper or lower limit.

[0127] In some embodiments, the heating rate of the second sintering is 2 to 10 °C / min, which can be 2, 3, 4, 5, 6, 7, 8, 9 or 10 °C / min, or any of the above values ​​as the upper or lower limit.

[0128] In some embodiments, the second sintering time is 2 to 10 hours, which can be 2, 5 or 10 hours, or any of the above values ​​can be the upper or lower limit of the range.

[0129] In some embodiments, the atmosphere for the second sintering is pure oxygen.

[0130] This invention, by limiting parameters such as the temperature, time, and heating rate of the second sintering, facilitates the obtaining of a more complete phosphate coating layer.

[0131] The present invention also provides a lithium-ion battery comprising the above-described ternary cathode material or the ternary cathode material prepared by the above-described preparation method.

[0132] In some embodiments, the lithium-ion battery further includes a negative electrode material, a separator, an electrolyte, and a casing. The present invention does not impose any special limitations on the negative electrode material, separator, electrolyte, and casing, and any negative electrode material, separator, electrolyte, and casing known to those skilled in the art can be used.

[0133] Unless otherwise specified, the range values ​​mentioned in this invention include the endpoint values. For example, 1 to 3 refers to the range values ​​including 1 and 3.

[0134] To further illustrate the present invention, a detailed description is provided below with reference to embodiments. However, it should be understood that the following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described herein. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0135] Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to the conventional experimental steps or conditions described in the literature in this field.

[0136] Example 1

[0137] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, manganese sulfate, and ammonium fluoride was prepared in a molar ratio of 6:1:3:0.1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 The aforementioned precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 Li₂CO₃ was mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min, then placed in a muffle furnace and heated to 700 °C at 5 °C / min, and held for 10 h to obtain a fluorine-doped ternary cathode material. The above cathode material, ammonium dihydrogen phosphate, and aluminum sulfate were mixed in deionized water, and the material ratio was adjusted so that the mass percentage of aluminum phosphate in the product was 5%. After stirring at room temperature for 4 h, the mixture was heated to 80 °C and stirred continuously until the solution was completely evaporated. The mixture was then placed in a muffle furnace and heated to 500 °C at 5 °C / min, and held for 10 h to obtain LiNi. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @AlPO4.

[0138] Chemical testing: The positive electrode active material LiNi prepared above was subjected to chemical testing. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 AlPO4, conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150μm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode was then compacted on a roller press with appropriate spacing, and subsequently sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150 g / m². 2 The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0139] Example 2

[0140] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, manganese sulfate, and ammonium fluoride was prepared in a molar ratio of 6:1:3:0.1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 The aforementioned precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 Li₂CO₃ was mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min, then placed in a muffle furnace and heated to 700 °C at 5 °C / min, and held for 10 h to obtain a fluorine-doped ternary cathode material. The above cathode material, ammonium dihydrogen phosphate, and magnesium chloride were mixed in deionized water, and the material ratio was adjusted so that the mass percentage of magnesium phosphate in the product was 5%. After stirring at room temperature for 4 h, the mixture was heated to 80 °C and stirred continuously until the solution was completely evaporated. The mixture was then placed in a muffle furnace and heated to 500 °C at 5 °C / min, and held for 10 h to obtain LiNi. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 @Mg3(PO4)2.

[0141] Chemical testing: The positive electrode active material LiNi prepared above was subjected to chemical testing. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 Mg3(PO4)2, conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150μm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode was then compacted on a roller press with appropriate spacing, and subsequently sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150 g / m². 2The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0142] Example 3

[0143] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, manganese sulfate, and ammonium fluoride was prepared in a molar ratio of 6:1:3:0.15. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH) 1.985 F 0.015 The aforementioned precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 1.985 F 0.015 Li₂CO₃ was mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min, then placed in a muffle furnace and heated to 700 °C at 5 °C / min, and held for 10 h to obtain a fluorine-doped ternary cathode material. The above cathode material, ammonium dihydrogen phosphate, and aluminum sulfate were mixed in deionized water, and the material ratio was adjusted so that the mass percentage of aluminum phosphate in the product was 5%. After stirring at room temperature for 4 h, the mixture was heated to 80 °C and stirred continuously until the solution was completely evaporated. The mixture was then placed in a muffle furnace and heated to 500 °C at 5 °C / min, and held for 10 h to obtain LiNi. 0.6 Co 0.1 Mn 0.3 O 1.9925 F 0.015 @AlPO4.

[0144] Chemical testing: The positive electrode active material LiNi prepared above was subjected to chemical testing. 0.6 Co 0.1 Mn 0.3 O 1.9925 F 0.015AlPO4, conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was applied to Al foil using a 150µm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode was then compacted on a roller press with appropriate spacing, and subsequently sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150 g / m². 2 The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0145] Comparative Example 1

[0146] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 6:1:3. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH)2. The above precursor Ni... 0.6 Co 0.1 Mn 0.3 (OH)₂ and Li₂CO₃ were mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min, and then placed in a muffle furnace and heated to 700 °C at a rate of 5 °C / min, and held at that temperature for 10 h to obtain LiNi. 0.6 Co 0.1 Mn 0.3 O2.

[0147] Electrochemical testing: The positive electrode active material LiNi prepared above was subjected to... 0.6 Co 0.1 Mn 0.3 O2, conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150µm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode sheet was then compacted on a roller press with appropriate spacing, and subsequently sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150 g / m². 2The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0148] Comparative Example 2

[0149] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, manganese sulfate, and ammonium fluoride was prepared in a molar ratio of 6:1:3:0.1. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed clean and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 The aforementioned precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 Li₂CO₃ was mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min, and then placed in a muffle furnace and heated to 700 °C at a rate of 5 °C / min, and held at that temperature for 10 h to obtain the fluorine-doped ternary cathode material LiNi. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 .

[0150] Chemical testing: The positive electrode active material LiNi prepared above was subjected to chemical testing. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 Conductive carbon black and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto Al foil using a 150µm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode sheet was compacted on a roller press with appropriate spacing, and then sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150g / m². 2The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0151] Comparative Example 3

[0152] Material preparation: An aqueous solution of nickel sulfate, cobalt sulfate, and manganese sulfate was prepared in a molar ratio of 6:1:3. Sodium carbonate and ammonia were added to adjust the pH of the solution to 12. The solution was heated in a water bath at 60°C and stirred at 300 rpm for 1 hour. After aging for 12 hours, the mixture was vacuum filtered. The precipitate was washed and dried in an oven at 100°C for 12 hours to obtain the precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH)2. The above precursor Ni... 0.6 Co 0.1 Mn 0.3 (OH)₂ and Li₂CO₃ were mixed in a ball mill at a molar ratio of 1:0.51 at 1000 rpm for 10 min. The mixture was then placed in a muffle furnace and heated to 700 °C at 5 °C / min, and held for 10 h to obtain a ternary cathode material. The above cathode material, ammonium dihydrogen phosphate, and aluminum chloride were mixed in deionized water. The material ratio was adjusted so that the mass percentage of aluminum phosphate in the product was 5%. After stirring at room temperature for 4 h, the mixture was heated to 80 °C and stirred continuously until the solution was completely evaporated. The mixture was then placed in a muffle furnace and heated to 500 °C at 5 °C / min, and held for 10 h to obtain LiNi. 0.6 Co 0.1 Mn 0.3 O2@AlPO4.

[0153] Chemical testing: The positive electrode active material LiNi prepared above was subjected to chemical testing. 0.6 Co 0.1 Mn 0.3 O2@AlPO4, conductive carbon black, and binder were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was applied to Al foil using a 150µm doctor blade and then dried in a vacuum drying oven at 100℃ for 12 hours. The dried electrode was then compacted on a roller press with appropriate spacing, and subsequently sliced ​​using a punching machine to obtain positive electrode sheets with a diameter of 12mm, which were weighed using an electronic balance. The areal loading of the positive electrode sheet was controlled to be 130-150 g / m². 2The negative electrode uses lithium metal as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (EC to DMC mass ratio 1:1) is used as the electrolyte. The battery is assembled in a glove box and subjected to charge-discharge tests. The voltage range is 2.8–4.45 V, and the charge-discharge current density is 0.1 C.

[0154] The electrochemical performance of the batteries prepared in Examples 1-3 and Comparative Examples 1-3 is compared in Table 1.

[0155] Table 1

[0156]

[0157] As can be seen from Table 1, the batteries prepared in Examples 1-3 all had a higher retention rate after 100 cycles than the batteries prepared in Comparative Examples 1-3, and the amount of metal leaching after cycling was lower.

[0158] Among them, the cathode material prepared in Comparative Example 1 does not contain F element and phosphate coating layer, and the battery prepared from it has the highest transition metal dissolution amount of 249 ppm. The cathode material prepared in Comparative Example 2 contains F element doping but does not contain phosphate coating layer, and the cathode material prepared in Comparative Example 3 contains phosphate coating layer but does not contain F element doping. The dissolution amount of the batteries prepared in Comparative Examples 2 and 3 is reduced, but still higher than that of the batteries prepared in Examples 1 to 3. This shows that the technical solution of F doping and phosphate coating layer in this invention achieves a synergistic effect, which greatly reduces the dissolution amount of transition metal, and the reduction can reach about 50%.

[0159] Analysis of the battery capacity retention rate showed that the cathode material prepared in Comparative Example 1, which did not contain F element or phosphate coating, had the lowest capacity retention rate at 89.0%. The cathode material prepared in Comparative Example 2 contained F element doping but did not contain phosphate coating, while the cathode material prepared in Comparative Example 3 contained phosphate coating but did not contain F element doping. The capacity retention rates of the batteries prepared in Comparative Examples 2 and 3 were slightly improved, by 0.4% and 0.8%, respectively. In contrast, the capacity retention rates of the batteries prepared in Examples 1-3 were improved by 3.5%, 4.2%, and 7.1%, respectively, compared to Comparative Example 1, which were significantly better than materials that only underwent F doping or phosphate coating. This demonstrates that the technical solution of the present invention, which uses F doping and simultaneously adds a phosphate coating, achieves a synergistic effect, resulting in a significant improvement in the battery capacity retention rate.

[0160] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A ternary cathode material, characterized in that, It has the molecular formula shown in Formula I: LiNi a Co b Mn c O 2-0.5d F d @M x (PO4) y Formula I; In Equation I, 0 < d ≤ 0.02, a + b + c = 1; M is a metal ion; The valence state of M is z+, and x and y satisfy: x = 3y / z.

2. The ternary cathode material according to claim 1, characterized in that, 0.01≤d≤0.02。 3. The ternary cathode material according to claim 1, characterized in that, M is one or more of Al ions, Mg ions, Zr ions, and Ca ions.

4. The ternary cathode material according to claim 1, characterized in that, It has any of the following molecular formulas: LiNi 0.6 Co 0.1 Mr 0.3 O 1.995 F 0.01 @AlPO4、LiNi 0.6 Co 0.1 Mr 0.3 O 1.995 F 0.01 @Mg3(PO4)2、LiNi 0.6 Co 0.1 Mr 0.3 O 1.9925 F 0.015 @AlPO4。 5. The method for preparing the ternary cathode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1) In the presence of a precipitant and a complexing agent, Ni source, Co source, Mn source and F source are mixed and subjected to a co-precipitation reaction, and after aging, a fluorine-doped ternary precursor is obtained. S2) The above-mentioned fluorine-doped ternary precursor and Li source are mixed and sintered for the first time to obtain fluorine-doped ternary cathode material. S3) The above-mentioned fluorine-doped ternary cathode material is mixed with a phosphorus source and a metal source, and then sintered for a second time to obtain a ternary cathode material with a phosphate coating layer.

6. The preparation method according to claim 5, characterized in that, The precipitant is selected from one or more of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide; The complexing agent is selected from one or more of ammonia, ammonium bicarbonate, and citric acid; The Ni source is selected from one or more of nickel nitrate, nickel sulfate, and nickel chloride; The Co source is selected from one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride; The Mn source is selected from one or more of manganese nitrate, manganese sulfate, and manganese chloride; The F source is selected from one or more of ammonium fluoride, potassium fluoride, sodium fluoride, and magnesium fluoride.

7. The preparation method according to claim 5, characterized in that, The temperature of the coprecipitation reaction is 50–80°C; the time of the coprecipitation reaction is 1–2 hours. In the coprecipitation reaction, the pH value of the system is 10-13; The coprecipitation reaction was carried out under stirring conditions; The stirring speed is 100-400 rpm; The aging time is 10 to 24 hours.

8. The preparation method according to claim 5, characterized in that, The Li source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium acetate; The molar ratio of the fluorine-doped ternary precursor to the molar ratio of Li in the Li source is 1:(1~1.02); The phosphorus source is selected from one or more of diammonium hydrogen phosphate and diammonium dihydrogen phosphate; The metal source is selected from one or more of aluminum, zirconium, magnesium, and calcium sources; The aluminum source is selected from one or more of aluminum nitrate and aluminum sulfate; The zirconium source is selected from one or more of zirconium oxynitrate and zirconium oxide; The magnesium source is selected from one or more of magnesium nitrate and magnesium acetate; The calcium source is selected from one or more of calcium chloride, calcium hydroxide, and calcium oxide; The mass of the phosphate coating layer is 0 to 6% of the mass of the fluorine-doped ternary cathode material, and is not 0.

9. The preparation method according to claim 5, characterized in that, The temperature of the first sintering is 600-800℃; the heating rate of the first sintering is 2-10℃ / min; the time of the first sintering is 5-20h; and the atmosphere of the first sintering is pure oxygen. The temperature of the second sintering is 500-800℃; the heating rate of the second sintering is 2-10℃ / min; the time of the second sintering is 2-10h; and the atmosphere of the second sintering is pure oxygen.

10. A lithium-ion battery, characterized in that, Includes the ternary cathode material as described in any one of claims 1 to 4.